The indirect fiscal benefits of low-skilled immigration - Mark Colas; Dominik Sachs (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
Low-skilled immigrants indirectly affect public finances through their effect on native wages & labor supply. We operationalize this indirect fiscal effect in various models of immigration and the labor market. We derive closed-form expressions for this effect in terms of estimable statistics. Empirical quantifications for the U.S. reveal that the indirect fiscal benefit of one low-skilled immigrant lies between 770 and 2,100 annually. The indirect fiscal benefit may outweigh the negative direct fiscal effect that has previously been documented. This challenges the perception of low-skilled immigration as a fiscal burden.
Keywords: H20; J31; J62; J68; 330; Immigration; Fiscal Impact; General Equilibrium